MECHANISM FOR THE ELECTION OF LOCAL HEADS / DEPUTY CHAIRMAN THROUGH THE REGIONAL HOUSE OF REPRESENTATIVES BASED ON LAW NUMBER 10 OF 2016 - Harsinta; Hamza Baharuddin; M. Kamal Hidjaz (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal